Validity of Traditional Ceremony Based Herbarium of Munggah Molo in Jombang Regency - Warda Firdausi Azizah; Mucharommah Sartika Ami (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to validate the herbarium which was developed based on the assessment of herbarium expert and learning media expert. The types of plants used in the manufacture of this herbarium were the types of plants used in the Munggah Molo traditional ceremony in Jombang Regency. This study refered to the R&D model which consists of 10 stages, but only first five stages were used by researchers. The five stages were potential and problems, data collection, product design, design validation, and design revision. Interview guides and validation sheets were used as research instruments. The interview guide was used to collect data about the types of plants used in traditional ceremony of Munggah Molo in Jombang Regency. The validation sheets were used to determine the value and feasibility of the developed herbarium. The data obtained were analyzed descriptively. Herbarium expert gave a score of 80 so that the herbarium developed obtained the feasible criteria. Learning media expert gave a score of 95 so that the herbarium met the criteria very feasible. Both validator stated that the herbarium could be used as a biology learning media.